Long-term risk of colorectal cancer after negative colonoscopy - Brenner, Hermann; Chang-Claude, Jenny; Seiler, Christoph; Hoffmeister, Michael (Journal of clinical oncology, 2011)
Purpose - - Colonoscopy is thought to be a powerful and cost-effective tool to reduce colorectal cancer (CRC) incidence and mortality. Empirical evidence for overall and risk group-specific definition of screening intervals is sparse. We aimed to assess the risk of CRC according to time since negative colonoscopy, overall, and by sex, smoking, and family history of CRC, in a large population-based case-control study. - - Patients and Methods - - In all, 1,945 patients with CRC and 2,399 population controls were recruited in 22 hospitals and through population registers in the Rhine-Neckar region of Germany from 2003 to 2007. Data on history of colonoscopy and important covariates were obtained by personal interviews and from medical records. - - Results - - Compared with people who had never undergone colonoscopy, people with a previous negative colonoscopy had a strongly reduced risk of CRC. Adjusted odds ratios for time windows of 1 to 2, 3 to 4, 5 to 9, 10 to 19, and 20+ years after negative colonoscopy were 0.14 (95% CI, 0.10 to 0.20), 0.12 (95% CI, 0.08 to 0.19), 0.26 (95% CI, 0.18 to 0.39), 0.28 (95% CI, 0.17 to 0.45), and 0.40 (95% CI, 0.24 to 0.66), respectively. Low risks even beyond 10 years after negative colonoscopy were observed for both left- and right-sided CRC and in all risk groups assessed except current smokers, who had a risk similar to that of never smokers with no previous colonoscopy 10 or more years after a negative colonoscopy. - - Conclusion - - These results support suggestions that screening intervals for CRC screening by colonoscopy could be longer than the commonly recommended 10 years in most cases, perhaps even among men and people with a family history of CRC, but probably not among current smokers.
Gesehen am 22.06.2022